2006
DOI: 10.1007/s00439-006-0249-3
|View full text |Cite
|
Sign up to set email alerts
|

The GAA triplet-repeat is unstable in the context of the human FXN locus and displays age-dependent expansions in cerebellum and DRG in a transgenic mouse model

Abstract: Friedreich ataxia (FRDA) is caused by homozygosity for FXN alleles containing an expanded GAA triplet-repeat (GAA-TR) sequence. This expanded GAA-TR sequence is unstable in somatic cells of FRDA patients, showing age-dependent expansions in dorsal root ganglia (DRG), the tissue where pathology occurs earliest and is most significant. This is thought to be the basis for the progressive, tissue-specific pathology seen in FRDA, but the mechanism(s) for this somatic instability is unknown. We show that transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 43 publications
5
62
0
Order By: Relevance
“…8A). Our results are in accordance with those obtained in animal models of different polyQ diseases, in which age has been described as a CAG repeat instability modifier (Clark et al, 2007;Ishiguro et al, 2001;Sato et al, 1999). Interestingly, we also observed that different tissues exhibited different patterns of MI increase with age.…”
Section: Tissue-and Age-dependent Somatic Mosaicism Of the Cag Repeatsupporting
confidence: 92%
“…8A). Our results are in accordance with those obtained in animal models of different polyQ diseases, in which age has been described as a CAG repeat instability modifier (Clark et al, 2007;Ishiguro et al, 2001;Sato et al, 1999). Interestingly, we also observed that different tissues exhibited different patterns of MI increase with age.…”
Section: Tissue-and Age-dependent Somatic Mosaicism Of the Cag Repeatsupporting
confidence: 92%
“…However, a somatic expansion bias exists within post-mitotic neurons of the spinal cord in FRDA patients (29) and mouse models (44,45). To investigate whether a lack of replication contributed to this bias, we performed parallel experiments with both dividing and non-dividing primary FRDA patient fibroblasts.…”
Section: Ectopic Expression Of Msh3 Is Sufficient To Induce Gaa⅐ttc Rmentioning
confidence: 99%
“…Three animal models are currently available for testing the in vivo efficacy of potential FXN activator molecules: these are the heterozygous [GAA·TTC] 230 KIKO (knock-in/knockout) and homozygous KIKI (knock-in) mice developed by Pandolfo and colleagues (Miranda et al, 2002), the human YAC FXN mouse developed by Pook and colleagues Clark et al, 2006), and the FXN-EGFP reporter mouse developed by Sarsero and colleagues (Sarsero et al, 2005;Sarsero et al, 2003). In the Pandolfo knock-in mice, a [GAA·TTC] 230 repeat was inserted into the mouse FXN locus at the position of the expansion in human FRDA alleles (FXN intron 1).…”
Section: Development Of Cell Lines and Mouse Models For Frdamentioning
confidence: 99%
“…Both transgenic lines exhibit intergenerational and age-related somatic instability of the repeat, with the most prominent expansions occurring specifically in the cerebellum (as seen in FRDA autopsy tissues) and in the dorsal root ganglia (DRG) Clark et al, 2006). By cross breeding the FXN YAC transgenic mice with heterozygous FXN knockout mice from Puccio and colleagues, the Pook laboratory has further shown that both transgenes are able to successfully rescue homozygous FXN knockout embryonic lethality and that the rescue mice exhibit an FRDA-like phenotype .…”
Section: Development Of Cell Lines and Mouse Models For Frdamentioning
confidence: 99%